Treatment approaches for elderly patients with complex proximal humerus fractures: A comparative study - Sunil H. Shetty; Shikhar D. Singh; Sarang Agrawal; Sameer S. A. Shaikh; Nrupam Mehta; Joydeep Kumar Dey; Abhilash Srivastava (MGM Journal of Medical Sciences)
Background: Proximal humerus fractures are typically minimally displaced and often result from low-energy trauma, particularly in elderly individuals with osteoporosis. In such cases, conservative or non-surgical treatments are generally effective. However, the optimal treatment approach remains an active research and debate area for fractures with moderate to severe displacement. Aims and Objectives: This study aims to conduct a comprehensive comparative analysis, focusing on evaluating and distinguishing the functional outcomes in elderly patients with complex proximal humerus fractures. Materials and Methods: A prospective, comparative study was conducted involving 60 elderly patients. The primary goal was to assess and compare the functional outcomes of complex proximal humerus fractures treated surgically using plating versus conservative treatment methods. Results: At the 8-week follow-up, patients in the non-surgical group demonstrated significantly lower average values for flexion, abduction, external rotation, and internal rotation than the surgical group. However, by the 6-month mark, no significant differences were observed between the two groups. Conclusion: The locking plate is a preferred implant for comminuted proximal humerus fractures. In this study, outcomes from locked plate fixation were comparable to those of non-operative treatments. Early initiation of physiotherapy and a robust rehabilitation program are crucial for achieving optimal functional recovery.